Orofacial complaints and complications of chemotherapy - Novaes, Cristina de Paula; Tristão e Silva, Rafaela; Coelho, Ângela Mello; Fabri, Gisele Maria Campos; Miranda Chaves, Maria das Graças Afonso (Archive of Oncology, 2017)
Background: Oral complications of chemotherapy are sometimes unnoticed and if not treated, they can compromise patients’ health and quality of life. Methods: This study aimed to assess and characterize orofacial complaints and complications, and their impact on the oral-health-related quality of life in patients undergoing cancer chemotherapy. Results: We evaluated 28 patients with solid tumors undergoing chemotherapy, through a systematic orofacial evaluation. Eighteen patients (64.2%) developed oral complications during chemotherapy and xerostomia scored the highest incidence n = 14 (50%). About oral health data, gingival index revealed greater part of patients classified with moderate or severe gingival inflammation. The mean plaque index was 25.6%. The mean CPOD index was 15.48 and was worse in patients without oral complications. The patients presented higher index of plaque and the oral health impact profile showed higher mean index in the patients group that developed oral complications. Conclusion: These data reinforce the crucial role of the dentist being in the multidisciplinary team, helping in the diagnosis of oral complications and provide a specific relieve of patient’s complaints, impacting positively on their quality of life.